Model Program Pembelajaran Bahasa Arab Non-Formal - Zaky, Ahmad; Ritonga, Ade Muhammad; Harahap, Muhammad Sapii (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
This article discusses the concept of Arabic language learning models applied to non-formal education, the method used to obtain data in this article is a literature review, the results of this article are useful as a reference for effective and efficient Arabic language learning for both formal and non-formal education. formal, this article also describes the appropriate approach to be taken in learning Arabic in the current era, this article also describes the steps that must be taken by teachers, educators, instructors and others, as a reference in adopting methods and techniques to achieve the goals desired Arabic language learning. It is hoped that the problems in learning Arabic both from a linguistic and non-linguistic perspective can be explained by carrying out further experiments and research. The author hopes that researchers, teachers and experts in Arabic language education will be able to continue researching, applying concepts to learning, as well as funding and budgeting. Arabic language learning project for this conceptualized model.